2020
DOI: 10.21450/rahis.v16i1.4947
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes Do Desempenho Econômico-Financeiro De Operadoras De Planos De Saúde

Abstract: O desempenho econômico-financeiro de organizações é amplamente estudado em finanças. Entretanto, o desempenho econômico-financeiro das Operadoras de Planos de Saúde (OPS) brasileiras não tem o destaque que merece frente à sua representatividade para a população. O setor de saúde suplementar brasileiro movimenta, em termos de receita bruta, cerca de 132 bilhões de reais anualmente e é responsável pela cobertura de saúde de mais de 24% da população do país. Diante desse contexto, a presente pesquisa teve como ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 8 publications
1
7
0
8
Order By: Relevance
“…The negative operating expenses and capital structure shows that health care providers that show a lack of control in their operating expenses and a large indebtedness tend to have a lower IDSS than OPS that have greater operational discipline and lower indebtedness, which confirms the findings of Xavier, Souza, and Avelar (2019) and Bragança et al (2019). While the former found that the decentralized action of the OPS increases operating expenses, the latter verified that the more indebted OPS are, the more prone they are to insolvency.…”
Section: Results and Analysessupporting
confidence: 75%
See 1 more Smart Citation
“…The negative operating expenses and capital structure shows that health care providers that show a lack of control in their operating expenses and a large indebtedness tend to have a lower IDSS than OPS that have greater operational discipline and lower indebtedness, which confirms the findings of Xavier, Souza, and Avelar (2019) and Bragança et al (2019). While the former found that the decentralized action of the OPS increases operating expenses, the latter verified that the more indebted OPS are, the more prone they are to insolvency.…”
Section: Results and Analysessupporting
confidence: 75%
“…The authors found that all indicators developed and all dummy variables adopted were significant in explaining the probability of insolvency of OPS. Xavier, Souza, and Avelar (2019) analyzed Brazilian OPS economic and financial performance from 2010 to 2015, considering operational, liquidity, indebtedness, and profitability indicators. The authors also analyzed non-financial indicators such as region, size, and type of provider.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Indeed, dental OPS have grown over 700.0% in terms of health plan beneficiaries since 2000 (ANS, 2018c). Still, many of these organizations experience economic and financial management problems, as shown by the Brazilian Association of Group Medicine -ABRAMGE (2015) and Xavier (2017). In addition, health plan operators' financial decisions are significantly influenced by National Supplementary Health Agency (ANS) strict regulations (Pinheiro, Peleias, Silva & Martins, 2015;Silva & Loebel, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…ANS data (2018c) indicate that over 47 million health plan beneficiaries use the supplementary health system -nearly 23.0% of the Brazilian population. While dental OPS serve nearly 22 million people (ANS, 2018c), they keep experiencing management problems (ABRAMGE, 2015;Xavier, 2017). In addition to existing challenges faced by health operators in Brazil, Varella and Ceschin (2014) emphasize that operators' unchanged behavior and regulation only exacerbate the already problematic situation.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the ANS (2018a) indicate that there are more than 47 million beneficiaries who use the supplementary health system, that is, almost 23% of the Brazilian population. However, many providers face management problems (Xavier, 2017). Moreover, in addition to the issues faced by health organizations in Brazil today, Varella and Ceschin (2014) point out that the situation tends to worsen if these organizations and regulators do not change their modus operandi.…”
mentioning
confidence: 99%